1991
DOI: 10.1002/hup.470060502
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of 5-HT uptake inhibitors

Abstract: The antidepressant efficacy of some of the newer 5-HT uptake inhibitors is reviewed on the basis of the available data. The placebo controlled evidence of efficacy of the 5-HT uptake inhibitors as a class is substantial with a broad range of antidepressant action and apparent equivalent efficacy to reference tricyclic antidepressants. Some selective advantage in treating anxiety or suicidal thoughts associated with depression is noted and the growing evidence of a unique selective role in treating obsessive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The serotonergic drugs employed in the present paradigm suppressed the immobility time in forced-swimming. These results are consistent with findings that serotonergic drugs are clinically active in the treatment of depression (1). It has been suggested that SSRIs are not effective in the forced-swimming test (8), and another report indicated that norepinephrine reuptake inhibitors, but not SSRIs are effective in this model (9).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The serotonergic drugs employed in the present paradigm suppressed the immobility time in forced-swimming. These results are consistent with findings that serotonergic drugs are clinically active in the treatment of depression (1). It has been suggested that SSRIs are not effective in the forced-swimming test (8), and another report indicated that norepinephrine reuptake inhibitors, but not SSRIs are effective in this model (9).…”
supporting
confidence: 90%
“…have established their status as effective antidepressants with effects comparable to the more traditionally used tricyclic and tetracyclic antidepressants (1). Furthermore, it is recognized that the binding sites for the antidepressant imipramine are the 5-HTreuptake pumps (2) and that 5-HT2 receptors are also down-regulated by the repeated administration of antidepressants (3).…”
mentioning
confidence: 99%
“…In addition, serotonin receptor activation increases anxiolytic-like behavioral responses, as measured by the elevated plus-maze test [ 22 ]. The number of marbles buried is reduced by benzodiazepine receptors agonist (diazepam) and serotonin reuptake inhibitors (fluoxetine and clomipramine) [ 23 ]. Spontaneous locomotor activity is also reduced by dopamine receptor blocking agents [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports indicate that because norfluoxetine has a long half-life of 10 days, a 5 week interval is recommended prior to initiating treatment with certain other agents, such as monoamine oxidase inhibitors (Montgomery, 1991), with which fluoxetine may have a toxic interaction.…”
Section: Discussionmentioning
confidence: 99%